Late chimerical status after bone marrow transplantation in severe aplastic anemia according to two different preparatory regimens - Marcia Quiroga; Noemi Farah Pereira; Marco Antonio Bitencourt; Carmem Bonfim; Marianna Gendre de Mesquita Monteiro; Ricardo Pasquini (Hematology, Transfusion and Cell Therapy, 2018)
Background: This study investigated the influence of two conditioning regimens on the chimerical status of 104 patients with acquired severe aplastic anemia. Methods: Patients were monitored for at least 18 months after related bone marrow transplantation and reaching partial or complete hematologic recovery. Group I patients (n = 55) received 200 mg/kg cyclophosphamide alone and Group II (n = 49) received 120 mg/kg cyclophosphamide associated with 12 mg/kg busulfan. Patients were classified in three chimerism levels according to the percentage of donor cells in the peripheral blood. Results: Chimerism ≤50% occurred in 36.4% of Group I and none of Group II; chimerism 51–90% was found in 20.0% of Group I and 10.2% of Group II; and chimerism >90% was found in 43.6% of Group I versus 89.8% of Group II. A significant association (p-value < 0.001) was found between conditioning type and chimerism levels. A higher number of infused cells was associated with higher levels of chimerism only in Group I (p-value = 0.013). Multivariate analysis showed that chimerism >90% is associated with the cyclophosphamide plus busulfan conditioning (p-value < 0.001) and higher number of infused cells (p-value = 0.009), suggesting that these factors are predictive of graft outcome. Regarding hematological recovery, higher chimerism levels were associated with higher neutrophil (p-value = 0.003) and platelet counts (p-value < 0.001) in Group I only. These results show that myeloablative conditioning favors full donor chimerism and non-myeloablative conditioning predisposes to mixed chimerism or autologous recovery of hematopoiesis. Conclusion: These data show that autologous recovery depends on the intensity of immunosuppression and that the immunosuppressive function of cyclophosphamide alone can induce this type of hematopoietic recovery. Keywords: Severe aplastic anemia, Bone marrow transplantation, Conditioning regimen, Chimerism